Perancangan Sistem Basis Data pada Klinik - Indrajani Indrajani (Bina Nusantara University, 2011)
The purpose of this research is to analyze and design a database to support Clinic information needs. The methods used in this research are data collection, which uses the search data techniques that includes interviews, documentation, observation, literature study, analysis method and database design that includes conceptual, logical, and physical design. The result of this research is a database system that can save data integrated, clinic information needs, and health services improvement which are patients and community in general. The conclusions that can be drawn from this research are the existence of this database system, so the clinic can manage patient data and checkup transaction, treatment, and payment.